Evaluación de calidad del sistema de seguimiento de tesis en la dirección de investigación de la FISI - UNAP - Tuanama Rojas, Llojana (2021)
The purpose of the research presentation was to evaluate the quality in use of a monitoring system for projects and final thesis reports implemented in the Research Directorate of the FISI - UNAP, for which the quality assessment tools were taken into account of the international standards related to the quality of software use: ISO / IEC 9126 - Product Quality and IRAM-ISO / IEC 14598 - Software Product Evaluation, given that to date no monitoring software had been used in said address, despite the fact that on two occasions there was the possibility of implementing a system of this type but that finally they were not received by the end users; Then our research provides a technical explanation of the problem and / or inconveniences that existed, detecting its weaknesses and providing feedback to the process for continuous improvement through valid alternatives that finally allowed us to have a thesis monitoring system that was so much needed in the Directorate of Investigation of the FISI - UNAP. The research has a quantitative approach at the applicative level with an experimental design of the pre-experimental type in addition to being transactional since the information was taken in a single moment, having as population and sample the end users of the Research Directorate of the FISI - UNAP that in total there are six (6) users. Finally, the information from the evaluation sheets was processed, observing favorable acceptance results of up to 87% equivalent to a planned level according to the evaluation rating assigned to the metrics of the quality characteristics in use, the same that allowed us to contrast and accept our alternative hypothesis; In addition, for continuous improvement in the monitoring processes, we have developed a cause and effect analysis with the Ishikawa diagram so that users can take it into account.